2020
DOI: 10.7759/cureus.9371
|View full text |Cite
|
Sign up to set email alerts
|

Lambl's Excrescences Associated With Left Frontal Ischemic Stroke: A Case Report

Abstract: Lambl's excrescences (LEs) are thin filiform strands of connective tissue found on the closure line of valves. Their exact etiology is unknown, and most of them are typically asymptomatic. We present a case of a 33-year-old African American male with a history of right upper extremity weakness that resolved on its own within a few minutes. On physical examination, no focal neurologic deficit was observed. MRI brain showed a tiny curvilinear focus of restricted diffusion with subtle T2-FLAIR hyperintensity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…12 While most LEs are asymptomatic and found incidentally on echocardiography or autopsy, they are considered as a rare cause of thromboembolism, commonly from the aortic valve, either through fragmentation or microthrombi formation on top of the lesions, leading to ischemic stroke, TIA, acute coronary syndrome, or peripheral thromboembolism (retinal, renal, popliteal). [1][2][3][4][5][6][7][8][9][10][12][13][14][15][16][17] A study involving 224 patients with recent stroke and 85 controls found LE present in 74 patients (33%) compared to only 6 patients (7.1%) from the control group. 18 It was concluded that LE is strongly associated with recent ischemic strokes in a multivariate analysis (odds ratio: 6.93, 90% confidence interval: 3.18-15.12; P-value < .001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 While most LEs are asymptomatic and found incidentally on echocardiography or autopsy, they are considered as a rare cause of thromboembolism, commonly from the aortic valve, either through fragmentation or microthrombi formation on top of the lesions, leading to ischemic stroke, TIA, acute coronary syndrome, or peripheral thromboembolism (retinal, renal, popliteal). [1][2][3][4][5][6][7][8][9][10][12][13][14][15][16][17] A study involving 224 patients with recent stroke and 85 controls found LE present in 74 patients (33%) compared to only 6 patients (7.1%) from the control group. 18 It was concluded that LE is strongly associated with recent ischemic strokes in a multivariate analysis (odds ratio: 6.93, 90% confidence interval: 3.18-15.12; P-value < .001).…”
Section: Resultsmentioning
confidence: 99%
“…According to the Centers for Disease Control and Prevention (CDC), ischemic pathologies contribute to 87% of strokes in the United States, of which 14%-30% are found to be from a cardiac source, while 24%-28% are cryptogenic in origin. 1 , 2 Lambl’s Excrescences (LEs) were first reported in 1856 by the physician Vilém Dušan Lambl. 3 They are rare single or multiple thin linear mobile fibrous threads originating at valve leaflets closure margins usually at the Arantius nodules, measuring ⩽2 mm in thickness and ⩾3 mm in length without gender predominance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation